Mudanças de código em eventos de fala na língua Tapirapé durante interações entre crianças - Paula, Luiz Gouvêa de (2001)
In this study we analyze the insertions of Portuguese borrowings and codeswitchings into Tapirapé language. Our aim was to analyze some phonologic, morphologic and syntactic processes, as well as the pragmatic ones throughout child speech data relating them to possible linguistic displacements that could lead the Portuguese language to definitively substitute the indigenous language. In this analysis we have established connections among the displacement processes and the social changes experienced by the Tapirapé indigenous people as a consequence of the asymmetric distribution of power among dift'erent societies. The theoretical basis of this study results írom the theories of bilingualism and the social and historical approaches proposed by Hamel (1988 on) who sees language contact as a conflicting relationship among indigenous and dominant societies. On the one hand, the results of our research point out to a tendency of displacement characterized in the linguistic level by the insertions of Portuguese. On the other hand there are evidences of the resistance of the indigenous language sustained by traditional practices and identity valúes.